Integrasi Tasawuf dalam Tradisi Kejawen Persaudaraan Setia Hati Terate - Sutoyo Sutoyo (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2014)
This article discusses the origins of the doctrine of PSHT Madiun; the patterns of integration of Sufism teaching into traditional Javanese mysticism (kejawen) at PSHT Madiun; and the teachings of PSHT Madiun during the two leadership periods of R.M. Imam Kusupangat and H. Tarmaji Budi Harsono. The results of this study indicate that: (1) the spiritual teachings of PSHT Madiun are founded on the teachings of Sufism; (2) the pattern of integration between Sufism and the traditional Javanese mysticism in PSHT Madiun is similar to the pattern used by Walisongo in spreading Islam in Indonesia, particularly in Java Island, by using local wisdoms. The accommodation of local wisdoms has two objectives, are to avoid hurting the heart of the local community and at the same time people are willing to practice Islamic teachings. Likewise, the leaders of PSHT Madiun have formulated their teachings by using what so-called ke-ESHA-an, so that the students of PSHT can willingly practice the teachings; (3) there are a number of differences in the way Kusupangat and Harsono lead this organization. Javanese mysticism aspect was dominating the teachings of PSHT during Kusupangat’s leadership while Harsono’s leadership shows how the Islamic nuance has been dominating over the teachings of PSHT. Keywords: Tasawuf, kejawen, PSHT, ke-ESHA-an.